Impact of Investing in Research and Development on Performance of IT Sector: An Empirical Analysis from Pakistan (2020-2024) - Osama Ali Haider; Muhammad Zeeshan; Dr. Muhammad Muzammil (ACADEMIA International Journal for Social Sciences, 2025)
This study examines how investment in research and development (R&D) affects company performance. Purpose is to explore financial impact of R&D spending measured by profitability metrics such as Return on Equity (ROE), Return on Assets (ROA), and Earnings Per Share (EPS). Using secondary data and econometric analysis, Study provides insights effectiveness of R&D as a strategic tool for growth. Study suggest a positive and significant relationship between R&D and ROE, although effects on EPS and ROA are not statistically significant. ROE is the most consistent predictor among three variables tested. Researchers and resources dedicated to R&D in Pakistan is also low. This Study supports argument that regular and well-managed R&D investment is important for maintaining a firm’s innovation capacity and attaining superior financial outcomes in today’s dynamic business atmosphere.